2021
DOI: 10.3389/fpls.2021.630413
|View full text |Cite
|
Sign up to set email alerts
|

Maize Ethylene Response Factor ZmERF061 Is Required for Resistance to Exserohilum turcicum

Abstract: Plants have evolved a series of sophisticated defense mechanisms to help them from harm. Ethylene Response Factor (ERF) plays pivotal roles in plant immune reactions, however, its underlying mechanism in maize with a defensive function to Exserohilum turcicum (E. turcicum) remains poorly understood. Here, we isolated and characterized a novel ERF transcription factor, designated ZmERF061, from maize. Phylogenetic analysis revealed that ZmERF061 is a member of B3 group in the ERF family. qRT-PCR assays showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 92 publications
(153 reference statements)
0
12
0
Order By: Relevance
“…The SA signalling pathway is associated with biotrophic pathogen attack, while the JA/ET signalling pathway is connected to attacks from necrotrophic pathogens (Pieterse et al, 2012); ERF genes contribute to immune responses through both these pathways (Zang et al, 2021). In our study, the transcript levels of VaERF16 increased after treatments with MeJA and ethephon at different time points (Figure b,d), suggesting that VaERF16 may be involved in JA/ET‐related defence signalling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SA signalling pathway is associated with biotrophic pathogen attack, while the JA/ET signalling pathway is connected to attacks from necrotrophic pathogens (Pieterse et al, 2012); ERF genes contribute to immune responses through both these pathways (Zang et al, 2021). In our study, the transcript levels of VaERF16 increased after treatments with MeJA and ethephon at different time points (Figure b,d), suggesting that VaERF16 may be involved in JA/ET‐related defence signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ERF96 from A. thaliana increases the transcript levels of the JA/ET defence‐related genes by binding to GCC motifs in their promoters, thereby enhancing resistance to necrotrophic pathogens (Catinot et al, 2015). Biochemical assays revealed that ERF11 binds to the GCC box of the BT4 promoter during the BT4 ‐regulated Arabidopsis defence response to hemibiotrophic bacterial pathogens (Zheng et al, 2019), and in maize, ZmERF061 and ZmERF105 function as transcriptional activators by specifically binding to GCC box elements (Zang et al, 2020, 2021). In the present research, we identified a GCC box (AGCCGCCA) and a possible DNA‐binding sequence (AGCAGCCC) in the VaPDF1.2 promoter and found that VaERF16, but not VaMYB306, bound to the VaPDF1.2 promoter (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…It should be pointed out that Zang et al (2021) evaluated the early stages of E. turcicum infection (from 10 to 72 h after inoculation) in contrast to the present study, which evaluated ET production from 4 to 16 dai when the fungus was found at its necrotrophic phase (beginning of leaf tissue chlorosis at 4-8 dai and necrosis at 12-16 dai).…”
Section: Activities Of Defence Enzymesmentioning
confidence: 90%
“…On the other hand, Zang et al (2021) isolated and characterized a novel ET response factor designated as ZmERF061 in maize plants that is strongly induced by E. turcicum infection as well as by SA and methyl JA. According to the authors, zmerf061 mutant maize lines became susceptible to NCLB due to lower expression of ZmPR10.1 and ZmPR10.2 genes and reduced activities of antioxidant enzymes.…”
Section: Activities Of Defence Enzymesmentioning
confidence: 99%
“…The V3 seedlings were sprayed with 100 µM ABA (Song et al, 2018) and 0.1 mM methyl jasmonate (MeJA; Zang et al, 2021) and sampled at 12 h after treatment. ABA and MeJA were dissolved in dimethyl sulphoxide (DMSO) and sterile water, respectively; controls were named DMSO for ABA and CK for MeJA.…”
Section: Methodsmentioning
confidence: 99%